Resected pancreatic adenocarcinoma: An Asian institution's experience. Issue 5 (3rd May 2021) - Ng, Kennedy Yao Yi; Chow, Edwin Wei Xiang; Jiang, Bochao; Lim, Cindy; Goh, Brian Kim Poh; Lee, Ser Yee; Teo, Jin Yao; Tan, Damien Meng Yew; Cheow, Peng Chung; Ooi, London Lucien Peng Jin; Chow, Pierce Kah Hoe; Lee, Joycelyn Jie Xin; et al.
Abstract: Background: Pancreatic adenocarcinoma (PDAC) is highly lethal. Surgery offers the only chance of cure, but 5‐year overall survival (OS) after surgical resection and adjuvant therapy remains dismal. Adjuvant trials were mostly conducted in the West enrolling fit patients. Applicability to a general population, especially Asia has not been described adequately. Aim: We aimed to evaluate the clinical outcomes, prognostic factors of survival, pattern, and timing of recurrence after curative resection in an Asian institution. Methods and Results: The clinicopathologic and survival outcomes of 165 PDAC patients who underwent curative resection between 1998 and 2013 were reviewed retrospectively. Median age at surgery was 62.0 years. 55.2% were male, and 73.3% had tumors involving the head of pancreas. The median OS of the entire cohort was 19.7 months. Median OS of patients who received adjuvant chemotherapy was 23.8 months. Negative predictors of survival include lymph node ratio (LNR) of >0.3 (HR = 3.36, P = .001), tumor site involving the body or tail of pancreas (HR = 1.59, P = .046), presence of perineural invasion (PNI) (HR = 2.36, P = .018) and poorly differentiated/undifferentiated tumor grade (HR = 1.86, P = .058). The median time to recurrence was 8.87 months, with 66.1% and 81.2% of patients developing recurrence at 12 months and 24 months respectively. The most common site of recurrence was the liver. Conclusion: The survival of Asian patients with resected PDAC who received adjuvant chemotherapy is comparable to reported randomized trials. Clinical characteristics seem similar to Western patients. Hence, geographical locations may not be a necessary stratification factor in RCTs. Conversely, lymph node ratio and status of PNI ought to be incorporated.